2002
DOI: 10.1172/jci13292
|View full text |Cite
|
Sign up to set email alerts
|

Acid incubation reverses the polarity of intercalated cell transporters, an effect mediated by hensin

Abstract: Metabolic acidosis causes a reversal of polarity of HCO3– flux in the cortical collecting duct (CCD). In CCDs incubated in vitro in acid media, β-intercalated (HCO3–-secreting) cells are remodeled to functionally resemble α-intercalated (H+-secreting) cells. A similar remodeling of β-intercalated cells, in which the polarity of H+ pumps and Cl–/HCO3– exchangers is reversed, occurs in cell culture and requires the deposition of polymerized hensin in the ECM. CCDs maintained 3 h at low pH ex vivo display a rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…It was previously reported that type B cells might serve as stem cells and give rise to both type A cells and principal cells. 21,22 However, the striking increase in the number of type A cells cannot be explained by conversion of type B IC, because the proportion of type B cells in the OMCD is very low. Moreover, BrdU incorporation was not detected in type B cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that type B cells might serve as stem cells and give rise to both type A cells and principal cells. 21,22 However, the striking increase in the number of type A cells cannot be explained by conversion of type B IC, because the proportion of type B cells in the OMCD is very low. Moreover, BrdU incorporation was not detected in type B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whether altered cell proliferation rates may contribute to the cellular remodeling of the CS epithelium during changes in systemic acid/base homeostasis (Yasoshima et al 1992;Tsuruoka and Schwartz 1996) or during carbonic anhydrase inhibition (Bagnis et al 2001) remains to be analyzed. Some studies (FejesToth and Naray-Fejes-Toth 1992; Yasoshima et al 1992;Schwartz et al 2002) did also suggest that some changes in the prevalence of a particular IC cell subtype might be related to the conversion of one cell type to the other (e.g., from type A IC cells to non-type A IC cells).…”
Section: Discussionmentioning
confidence: 99%
“…Both pendrin and the putative apical anion exchanger of the type B intercalated cell transport Cl -and HCO 3 -. 8,29 Both apical anion-exchange activity and pendrin protein expression are downregulated in models of metabolic acidosis, eg, with NH 4 Cl ingestion, [12][13][14]30,31 and are upregulated in models of metabolic alkalosis, eg, with NaHCO 3 ingestion. [12][13][14] Apical anion exchange in the CCD is also upregulated by DOCP.…”
Section: Verlander Et Al Mineralocorticoids Upregulate Pendrin In Moumentioning
confidence: 99%